The Implementation of Guided Inquiry Learning Model with Edmodo to Improve Students’ Learning Outcomes on Acid-Based Subject Matter - Hasrilia Beskara; Muhammad Danial; Taty Sulastry (PAEDAGOGIA, 2024)
This study aims to determine whether guided inquiry learning assisted by Edmodo can improve the learning outcomes of high school students on acid-base subject matter. The research method used is a quasi-experiment with a quantitative approach; the research design used is a posttest-only control group design. The research subjects were students of class XI MIPA 5 (experimental group), consisting of 29 students, and class XI MIPA 6 (control group), consisting of 26 students. Data collection techniques used learning outcome tests and observation sheets to implement the learning process. The results of descriptive analysis showed that the experimental class obtained an average value of learning outcomes higher than the control class, which amounted to 81.3 for the experimental class and 71.5 for the control class. The results of inferential statistical analysis of student learning outcomes showed that the data of the two groups were not normally distributed and came from a homogeneous population. Hypothesis testing using the Mann-Whitney test obtained asymp. Sig. < α (0.001 < 0.05) so that H0 is rejected and Ha is accepted. Therefore, guided inquiry learning assisted by Edmodo can improve the learning outcomes of high school students on acid-base subject matter.